Проблеми легітимації земельних торгів (аукціонів) як віддзеркалення правового еігілізму в діяльності суб'єктів владних повноважень - Бєлкін, Л. М.; Белкин, Л. М.; Belkin, L. (My University, 2011)
In article in a historical context problem of legalization of the ground auctions (auctions), connected, on the one hand, with imperfection and discrepancy of the current legislation of Ukraine, and on the other hand, with aspiration of subjects of imperious powers to bypass a lawful order of a solution of a problem are considered. It is shown that carrying out of such auctions out of sphere of regulation by laws creates threat of revision of the concluded contracts for the purchaser of the rights to the earth.
Бєлкін Л. М. Прогблеми легітимації земельних торгів (аукціонів) як віддзеркалення правового нігілізму в діяльності суб'єктів владних повноважень / Л. М. Бєлкін // // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2011. - Вип. 41. - С.268-276.
Keywords: легітимація земельних торгів; земельні торги; земельні відносини; аукционы как отражение правового нигилизма; земельные торги; земельные отношения; аукціони як відзеркалення правового нінілізму; легитимация земельных торгов; auctions as a reflection of legal nihilism; land auction; land relations